Facade, Neville House - Ghosh, Ayan (2023)
Neville House is the headquarter of Bombay Dyeing and Co; Manufacturing Company Ltd., the flagship company of the Wadia Group, founded in 1736 by Lovji Nusserwanjee Wadia, considered the founder of the shipbuilding industry in Mumbai. The Bombay dry dock, the first dry dock in Asia, was built by Lovji Wadia and his brother Sorabji Wadia in 1750.